Making Publics, Making Places - Barbour, Kim; Griffiths, Mary (University of Adelaide Press, 2016)
This book focuses on the surprising generative possibilities which digital and smart technologies offer media consumers, citizens, institutions and governments in making publics and places, across topics as diverse as Twitter audiences, rural news, the elasticity of the public sphere, Weibo, cultural heritage and responsive spaces in smart cities. Multidisciplinary perspectives engage with critical questions in new media scholarship. General readers, curious about how technologies are enabling social, public and civic participation, will enjoy the book's mix of fresh approaches and insights.